The use of Burmester curves in combination with the least square method in the design of the Stephenson-I type mechanism - Pira, Bujar; Topilla, Labinot (Zielona Góra: Uniwersytet Zielonogórski)
This paper provides a brief description of an approach that utilises Burmester curves in designing six-bar mechanisms that prescribe five precision points. This approach combines the Freudenstein method and the least square method with Burmester theory. With this paper, we demonstrate the application of this combined approach in designing Stephenson type-I six-bar planar mechanisms that prescribe five positions, using a specific case study.
Keywords: Burmester; mechanism; design; least square; six-bar